A case study of dietary cereal demand forecasts for Neo infantile atrophy. Issue 5 (4th July 2021) - Mei, Cheng; Chou, Li-Wei; Lin, Jaung-Geng
Abstract: Medical literature emphasizes, "Every medicine has its side effects". Therefore, we have to pay more attention in advocating preventive medicine today. Above all, Huangdi neijing emphasizes the principle of "governance to avoid illness "and supporting the "Five grains for nourishment, as early as 3700 years ago. Since the beginning of this year, we have witnessed the global pandemic of Corona virus followed by floods, droughts and other natural disasters all over the world. Meanwhile food scarcity, as Brown et al. (2004) have warned, continues to scare people in China. There are rumors that Chinese people will consume all the food in their country have not subsided. Whether or to what extent this will affect diet therapy and survival, especially the sequelae of Neo infantile atrophy and the healthy diet of chronic patients remains to be seen. This article specifically focuses on China's staple demand forecasting. This research has indicated that food security and sufficiency continue to be an important subject worthy of our attention.